2008
DOI: 10.1152/ajpregu.00465.2007
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous opioids: role in prostaglandin-dependent and -independent fever

Abstract: This study evaluated the participation of -opioid-receptor activation in body temperature (T b) during normal and febrile conditions (including activation of heat conservation mechanisms) and in different pathways of LPS-induced fever. The intracerebroventricular treatment of male Wistar rats with the selective opioid -receptor-antagonist cyclic D-Phe-Cys-Try-DTrp-Arg-Thr-Pen-Thr-NH2 (CTAP; 0.1-1.0 g) reduced fever induced by LPS (5.0 g/kg) but did not change Tb at ambient temperatures of either 20°C or 28°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 56 publications
2
24
0
1
Order By: Relevance
“…Nevertheless, it is clear from the results of our study and from the results of mammalian studies that IL-6 and PGs are not exclusively responsible for LPS-induced fevers. Macrophage inflammatory protein-1␤, corticotropin-releasing factor, and endothelin-1 have been identified as PG-independent mediators of fever in mammals (11,12). In addition, Fraga et al (12) showed that, in mammals, LPS and endogenous pyrogens (except IL-1␤ and PGs) recruit the opioid system to cause a -receptor-mediated fever independent of PG.…”
Section: Absence Of Pge 2 In Csf Of Lps-treated Pekin Ducksmentioning
confidence: 99%
“…Nevertheless, it is clear from the results of our study and from the results of mammalian studies that IL-6 and PGs are not exclusively responsible for LPS-induced fevers. Macrophage inflammatory protein-1␤, corticotropin-releasing factor, and endothelin-1 have been identified as PG-independent mediators of fever in mammals (11,12). In addition, Fraga et al (12) showed that, in mammals, LPS and endogenous pyrogens (except IL-1␤ and PGs) recruit the opioid system to cause a -receptor-mediated fever independent of PG.…”
Section: Absence Of Pge 2 In Csf Of Lps-treated Pekin Ducksmentioning
confidence: 99%
“…injected zymosan. We previously found that eOPs participate in the febrile response that is induced by ET-1 and CRF but not prostaglandins [20]. Kanashiro et al [24] reported that ET-1 and CRF do not participate in the febrile response induced by i.a.…”
Section: Discussionmentioning
confidence: 87%
“…The CRF/ET-1 pathway is not involved in i.a. zymosan-induced fever [24], indicating that the eOPs are not released through the CRF or ET-1 during the febrile response; instead, they appear to be released through cytokines, such as TNF-α and IL-6 [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POMC peptide is a precursor for several biologically active neuropeptides including ␣-MSH, ␤-endorphin, and ACTH (40). Of particular interest to the current study is ␤-endorphin as blockade of -opioid receptor, one of the receptors for ␤-endorphin either by specific antagonists or genetic mutation abrogates the fever response induced by classical pyrogens including LPS (4,5,16,44,61) via several different mechanisms, including a central hypothermic action, peripheral vasodilation, and peripheral antipyretic activity (44).…”
Section: Discussionmentioning
confidence: 99%